Metal-free, intermolecular carbopyridylation of alkenes via visible-light-induced reductive radical coupling - Chen, Dan (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
An efficient, metal-free strategy for the intermolecular three-component carbopyridylation of styrenes, enabled by Hantzsch ester and visible light, has been described. This versatile protocol gives access to important β-CF(3) pyridines, through the regioselective, sequential formation of two C–C bonds without the use of exogenous catalysts. The value of this benign protocol has been demonstrated through functionalizations of natural-product- and drug-based complex molecules.